Promising vaccines for treating glioblastoma. (2nd November 2018) - Swartz, Adam M.; Shen, Steven H.; Salgado, Miguel A.; Congdon, Kendra L.; Sanchez-Perez, Luis
ABSTRACT: Introduction : Conventional therapies for glioblastoma (GBM) typically fail to provide lasting antitumor benefits, owing to their inability to specifically eliminate all malignant cells. Cancer vaccines are currently being evaluated as a means to direct the adaptive immune system to target residual GBM cells that remain following standard-of-care treatment. Areas covered : In this review, we provide an overview of the more noteworthy cancer vaccines that are under investigation for the treatment of GBM, as well as potential future directions that may enhance GBM-vaccine effectiveness. Expert opinion : To date, no cancer vaccines have been proven effective against GBM; however, only a few have reached phase III clinical testing. Clinical immunological monitoring data suggest that GBM vaccines are capable of stimulating immune responses reactive to GBM antigens, but whether these responses have an appreciable antitumor effect on GBM is still uncertain. Nevertheless, there have been several promising outcomes in early phase clinical trials, which lend encouragement to this area of study. Further studies with GBM vaccines are, therefore, warranted.